BUILDING MANAGEMANT SYSTEM BERBASIS ARDUINO DENGAN PROTOKOL KOMUNIKASI MODBUS - Gustiar; Krisna Pratama; Indra Dwisaputra; Surojo (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
A Building Management System (BMS) is a control and monitoring system used in a building. BMS aims to integrate all devices contained in a building. The application of this system in a building or building has benefits such as time and energy efficiency. In this BMS system, a controller module has been developed which is equipped with the Modbus protocol so that it can be connected to the Human Machine Interface (HMI) software to control and monitor a building. Controlled objects include turning on and off room lights through HMI and alarms if smoke is detected, while monitoring is focused on room temperature and energy use in a building. The use of this device begins with logging in to the HMI and continues by entering the ON/OFF control sub menu on the HMI. Energy meter and temperature data are displayed on the HMI and can be saved in Excel. The temperature sensor used has an accuracy rate of 99.8%. The communication process between the control module and the HMI can work well and has an average data transmission delay of 2.5 seconds.